Du contrôle des connaissances à l’évaluation de la compétence : changement de paradigme et modification des représentations - Bourguignon, Claire (Linguarum Arena, 2018)
This article will show that research on competence-oriented assessment does not meet the criteria of analytic research but is to be considered as systemic. Indeed, competence-oriented assessment is complex and marks a turning point in epistemology in the field of language learning and teaching. It thus upsets the traditional representations based on knowledge assessment. As a result, after presenting the fundamental concepts of competence-oriented assessment and its impact on language learning and teaching, we’ll explain why words are useless to make representations change. Teachers won’t apply a theoretical framework which does not fit in with their representation. This is why it seems difficult to envisage any research on competenceoriented assessment without reflecting on how teachers can adapt to a new paradigm.